Impaired fertility and perceived difficulties conceiving in Ghana: measurement problems and prospects - Fledderjohann, J; Johnson, D (Cambridge University Press, 2015)
What is the most appropriate measure of impaired fertility for understanding its social consequences in sub-Saharan Africa? The dearth of subjective measures in surveys in the region has prevented comparisons of subjective and objective measures. Perceived difficulties conceiving may have a greater impact than objective measures for social outcomes such as divorce, stigmatization and distress. This study compares 12- (clinical) and 24- (epidemiological) month measures from biomedicine and 5- and 7-year measures from demography with a subjective measure of impaired fertility using correlations, random effects models and test–retest models to assess relationships between measures, their association with sociodemographic characteristics and the stability of measures across time. Secondary panel data (1998–2004) from 1350 Ghanaian women aged 15–49 of all marital statuses are used. Longer waiting times to identification of impaired fertility required by demographic measures result in more stable measures, but perceived difficulties conceiving are most closely aligned with clinical infertility (r=0.61; p<0.05). Epidemiological infertility is also closely aligned with the subjective measure. A large proportion of those identified as having impaired fertility based purely on waiting times are successful contraceptors. Where subjective measures are not available, epidemiological (24-month) measures may be most appropriate for studies of the social consequences of impaired fertility. Accounting for contraceptive use is important in order to avoid false positives. Future research should consider a variety of measures of perceived difficulties conceiving and self-identified infertility to assess which is most valid; in order to accomplish this, it is imperative that subjective measures of infertility be included in social surveys in sub-Saharan Africa.